Interspeech 2017 2017
DOI: 10.21437/interspeech.2017-1514
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Properties of Canonical and Non-Canonical Stress in French, Turkish, Armenian and Brazilian Portuguese

Abstract: Languages are often categorized as having either predictable (fixed or quantity-sensitive) or non-predictable stress. Despite their name, fixed stress languages may have exceptions, so in fact, their stress does not always appear in the same position. Since predictability has been shown to affect certain speech phenomena, with additional or redundant acoustic cues being provided when the linguistic content is less predictable (e.g., Smooth Signal Redundancy Hypothesis), we investigate whether, and to what exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In languages with movable stress, such as Brazilian Portuguese (or English), its placement is relatively inconsistent and hence, much less predictable than in fixed-stress languages. This contrasts with languages with fixed stress, such as Armenian, Turkish or French studied in Athanasopoulou et al (2017) that canonically place lexical stress on a specified syllable. At the same time, fixed-stress languages also allow for some non-canonical placements that show degrees of predictability depending on the morphological and phonological aspects of stress location in that language.…”
Section: Language Specific Implementations Of the Surprisal-prosody Imentioning
confidence: 87%
See 2 more Smart Citations
“…In languages with movable stress, such as Brazilian Portuguese (or English), its placement is relatively inconsistent and hence, much less predictable than in fixed-stress languages. This contrasts with languages with fixed stress, such as Armenian, Turkish or French studied in Athanasopoulou et al (2017) that canonically place lexical stress on a specified syllable. At the same time, fixed-stress languages also allow for some non-canonical placements that show degrees of predictability depending on the morphological and phonological aspects of stress location in that language.…”
Section: Language Specific Implementations Of the Surprisal-prosody Imentioning
confidence: 87%
“…Recently, Athanasopoulou et al (2017) examined the fixed vs. movable phonological stress parameter as a manifestation of predictability. In languages with movable stress, such as Brazilian Portuguese (or English), its placement is relatively inconsistent and hence, much less predictable than in fixed-stress languages.…”
Section: Language Specific Implementations Of the Surprisal-prosody Imentioning
confidence: 99%
See 1 more Smart Citation
“…Armenian lacks common correlates found in final-iambic languages. For example, stress is quantity insensitive and phonetically cued by pitch (Athanasopoulou et al 2017). Turkish and French have stress patterns similar to Armenian and have been argued to lack feet (Özçelik 2017).…”
Section: Stress In Armenianmentioning
confidence: 99%
“…Uzbek and Turkish belong to the same (Turkic) language family and are described as having essentially the same type of stress system (i.e., canonical final stress with certain types of exceptions); however, it turns out that the acoustic properties of stress in the two languages differ considerably. Turkish, like other languages with predictable stress, tends to have relatively weak stress cues (e.g., Athanasopoulou et al 2017, Vogel 2020, exhibiting a minimal acoustic distinction of the final stressed syllable from the penult unstressed syllable. That is, it has been found that in languages with predictable stress, since the position of word stress is independently known, there is less need to enhance the stressed syllable than in languages with unpredictable stress such as Spanish and Greek (e.g., Vogel et al 2016, Ortega-Llebaría & Prieto 2010, Arvaniti 2007.…”
Section: Uzbek In the Context Of Predictable Turkic Stressmentioning
confidence: 99%